Aqueous-mediated selective reduction of Imidacloprid: a novel method for detoxification and detection - Gedam, Ashwin D.; Katiya, Manish M.; Dhonde, Madhukar G.; Ganorkar, Kapil S.; Thakare, Vijay J.; Jadhao, Nitin L.; Gajbhiye, Jayant M. (Journal of Environmental Chemical Engineering, 2026)
The extensive application of the neonicotinoid insecticide Imidacloprid has produced significant environmental concerns owing to its persistence and toxicity in aquatic ecosystems, thereby necessitating the development of straightforward and environmentally sustainable methods for its detection and detoxification. In the present study, we demonstrate for the first time that selective reducing agents can function as environmentally friendly chromogenic reagents for the detoxification and detection of Imidacloprid in contaminated water. The insecticide was treated with various reducing agents, such as aqueous solution of glucose, sodium sulphite, hydrazine hydrate, isoniazid, and vanillin, leading to the reduction of Imidacloprid and the formation of a white solid product. The reaction process provides a straightforward visual indication, suggesting the possible use of these reagents as eco-friendly chromogenic systems for pesticide monitoring. The chemical identification and structural properties of the resultant product were elucidated and confirmed by standard spectroscopy techniques. Moreover, the reaction pathway was systematically examined through experimental observations and theoretical studies. Density Functional Theory (DFT) calculations were conducted with the Gaussian program to provide a more profound understanding of the reaction pathway. The integrated experimental and computational findings offer a reliable mechanistic insight into the reduction process and highlight the potential of selective reducing agents as environmentally friendly reagents for the detection and detoxification of Imidacloprid in aquatic ecosystems.
Keywords: DFT analysis; Extracted Imidacloprid; glucose; Hydrazine hydrate; Isoniazid; Sodium sulphite; Vaniline